Evaluation of Phytochemistry and Antidiabetic Potential of an Astragalus Species (Astragalus kurdicus Boiss.) - Ozdemir, Kevser; Barak, Timur Hakan; Celep, Inci Kurt; Savasan, Ozan; Kayiran, Serpil Demirci; Ozkan, Esra Eroglu (Wiley-V C H Verlag Gmbh, 2024)
Astragalus kurdicus Boiss. roots are used in folk medicine for antidiabetic purposes. Different Astragalus plant metabolites have a notable potential for antidiabetic activity through varying mechanisms. Herein, this study is designed to assess the antidiabetic activity of Astragalus kurdicus total (AKM: methanol extract, yield: 14.53 %) and sub-extracts (AKB: n-butanol, AKC: chloroform, AKW: water, AKH: hexane extracts), utilizing a range of diabetes-related in vitro methodologies, and to investigate the chemical composition of the plant. The highest astragaloside and saponin content was seen in AKB extract. Among the measured saponins, the abundance of Astragaloside IV (27.41 mu g/mg in AKM) was the highest in high-performance thin-layer chromatography (HPTLC) analysis. Furthermore, flavonoid-rich AKC was found to be mostly responsible for the high antioxidant activity. According to the results of the activity tests, AKW was the most active extract in protein tyrosine phosphatase 1 B (PTP1B), dipeptidyl peptidase IV (DPP4), and alpha-amylase inhibition tests (percent inhibitions are: 87.17 %, 82.4 %, and 91.49 % respectively, at 1 mg/mL). AKM and AKW demonstrated the highest efficacy in stimulating the growth of prebiotic microorganisms and preventing the formation of advanced glycation end products (AGEs). Thus, for the first time, the antidiabetic activity of A. kurdicus was evaluated from various perspectives.
Keywords: Astragalus kurdicus; diabetes; HPTLC; DPP4; PTP1B; prebiotic